Factors influencing middle managers' commitment to the implementation of innovations in cancer care. Issue 2 (April 2019) - Urquhart, Robin; Kendell, Cynthia; Folkes, Amy; Reiman, Tony; Grunfeld, Eva; Porter, Geoff
Objective: To identify and illuminate influences on middle managers' commitment to innovation implementation. Methods: A qualitative study was conducted, employing the methods of grounded theory. Semi-structured interviews were used to collect data from middle managers (n = 15) in Nova Scotia and New Brunswick, Canada. Data were collected and analysed concurrently, using an inductive constant comparative approach. Data collection and analysis continued until theoretical saturation was reached. Results: The data revealed middle managers contemplate two central issues in terms of their commitment to implementation, that is whether or not they fully engage in and support the implementation of a particular innovation. These issues are (1) ease of implementation and (2) potential benefit for patients. Middle managers' views and expectations related to ease of implementation are influenced by available resources, fit with setting, and stakeholder buy-in. Their views on patient benefit are influenced by external evidence of benefit and local gaps in care. Conclusions: These findings provide further insight into the factors that influence middle managers' commitment to innovation implementation, and how middle managers consider these factors in the context of their work settings.